AMPLE: A Material Point Learning Environment. (January 2020) - Coombs, William M.; Augarde, Charles E.
Abstract: The Material Point Method (MPM) is a computational tool ideally suited to modelling solid mechanics problems involving large deformations where conventional mesh-based methods struggle. Explicit and implicit formulations are available, but for both the learning curve for understanding the method and arriving at a useful implementation is severe. Researchers must understand and implement finite element analysis, non-linear material behaviour, finite deformation mechanics and non-linear solution methods before they can even verify their formulations. This issue represents a significant barrier for post-doctoral researchers, graduate students and undergraduate students to start working with (and understanding) the method. This paper presents A Material Point Learning Environment (AMPLE) based around implicit variants of the method, with the aim of softening this steep learning curve via MATLAB-based, accessible and compact scripts. The code is freely available from github.com/wmcoombs/AMPLE .